Validation of plasma D-dimer in Chinese patients with acute non-ST segment elevation myocardial infarction - Fan, Xin; Min, Tingting; Su, Shaohui; Xiong, Bin; Wan, Huaibin (Frontiers in Cardiovascular Medicine, 2022)
Objective： To analyze the predictive values of D-dimer in Chinese patients with non-ST-segment elevation myocardial infarction (NSTEMI). Methods： We retrospectively retrieved consecutive hospitalized patients due to acute NSTEMI between January 2015 and December 2018 from the Electronic Medical Record library. The clinical and follow-up data were collected. The primary endpoint was the major adverse composite cardiovascular events (MACEs) including all-cause death, nonfatal myocardial infarction, and nonfatal stroke, and the secondary endpoints were all-cause death, nonfatal myocardial infarction, and nonfatal stroke. The Cox regression model was used to evaluate the association between risk factors and clinical outcomes in Chinese patients with NSTEMI. Results： A total of 676 patients were included, the median age was 64.0(53.0-75.0) years old,76.3% were males. Patients with higher D-dimers were fewer males, older, with higher Charlson comorbidity index, and had a higher incidence of MACEs (60.1% vs control 9.0%; P<0.001) and all-cause death (49.4% vs control 2.2%; P<0.001). Multivariate COX analysis suggested D-dimer level was an independent predictor of MACEs [HR: 1.095, 95% CI: 1.050–1.141, P<0.001]. ROC suggested that D-dimer levels were better than the Charlson comorbidity index in the MACEs and all-cause death. Conclusion： In Chinese patients with acute NSTEMI, higher D-dimer levels at admission suggest a poor long-term prognosis.